The effect of hypnosis on perceived stress in women with preeclampsia - Sedighe Vahdat; Mahdi Fathi; Zhaleh Feyzi; Mohammad Taghi Shakeri; Mahin Tafazoli (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Perceived stress is one of the causes of preeclampsia; one of the ways to manage mental stress is hypnosis. The aim of this study was to determine the effect of hypnosis on perceived stress in women with preeclampsia. MATERIALS AND METHODS: This randomized clinical trial was performed on 80 (40 people in each group) pregnant women 28-32 weeks with preeclampsia and hospitalized in two public hospitals in Mashhad in 2020. The Cohen Perceived Stress Questionnaire was first completed in two groups. Then, in the intervention group, three half-hour sessions of hypnosis were performed with an interval of 3 days (hypnosis consists of three sessions: each session is held for three consecutive nights). After each session, the intervention package, which included recording the dialogs of each session for posthypnotic suggestion, was delivered to the mothers on a CD to listen to every night before bed. The control group received routine care. Then, 2 weeks after the intervention, the Perceived Stress Questionnaire was completed by both groups. The results were analyzed by independent t-test, paired t-test, Mann-Whitney, Chi-square, Friedman and covariance tests, and by SPSS 16. RESULTS: At the beginning of the study, there was no statistically significant difference between demographic characteristics and the perceived stress score before the intervention between the two groups (P > 0.05). However, after the intervention, the mean perceived stress score was a statistically significant difference between the intervention and control groups (P = 0.005). Perceived stress after the intervention was significantly reduced in the intervention group, which was significant between the two groups. CONCLUSION: Perceived stress in mothers with preeclampsia is reduced by hypnosis.